Sindrom Lutembacher Sebuah Penilaian ekhokardiografi - Muhammad Barri Fahmi; Amiliana Mardiani; Ganesja M Harimurti (The Indonesian Heart Association, 2012)
Lutembacher’s syndrome (LS), consisted of Atrial Septal Defect(ASD) and Mitral Stenosis (MS), is a very rare form of cardiac anomaly. Rene Lutembacher’s first described this syndrome in 1916. Currently, any combination of ASD, congenital or iatrogenic and MS, acquired or congenital is referred as LS.By using echocardiography, the hemodynamic of LS could be assesed. Pathophysiologically, the hemodynamic of ASD is related to the magnitude and direction of shunting across the interatrial communication. The determinants of the amount of shunting are the defect size and theventricles relative resistance to inflow. In MS, the restricted in?low leads to increased diastolic pressures in the left ventricle. This resulted in marked accentuation of the left-to-right shunt.We reported a case of a 34 years old female, first came to Harapan Kita National Cardiac Center, in 2010. She was diagnosed with LS, and was planned to have ASD closure and mitral valve repair by surgery. However, she refused to undertake the procedure. In summary, to illustrate the interactions between ASD and MS, the presence of ASD underestimated the severi?y of MS; meanwhile the existence of MS magnified the left to right shunt in patients with ASD.